Finite Element Modeling of a Reinforced Concrete Frame with Masonry Infill and Mesh Reinforced Mortar Subjected to Earthquake Loading. Issue 1 (February 2016) - Redmond, Laura; Ezzatfar, Pourang; DesRoches, Reginald; Stavridis, Andreas; Ozcebe, Guney; Kurc, Ozgur
Failures of unreinforced masonry infill walls commonly occur during seismic events. One method of preventing such failures is the use of externally applied mesh reinforced mortar (MRM). This paper presents a finite element (FE) modeling scheme combining smeared crack and interface elements to simulate the seismic response of RC frames with hollow clay tile (HCT) infill and RC frames with HCT infill and MRM. The models can capture cracking patterns, timing of damages, and force-displacement behavior of the frames. A study modeling the plastering mortar with overlay elements and a transformed section approach suggests the latter gives more realistic predictions for initial stiffness and drift at peak strength. Parametric studies on the influence of dowel area and the placement of dowels indicate that there are diminishing returns in increasing the dowel area and that the connections must be present on both the top and bottom of the infill walls to be effective.